PEMENUHAN KEBUTUHAN TIDUR TERHADAP TINGKAT DEPRESI LANSIA DI UPT PSLU BONDOWOSO - Ady Hamsyah Maulana (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2015)
In UPT PSLU Bondowoso 55.55% had bad sleep and 44.44% had good sleep. This study is to determine the relationship between the fulfillment of sleep needs and the level of depression in the elderly in UPT PSLU Bondowoso. This type of correlational research with obsevasional design. Samples of research as many as 74 elderly using simple random sampling technique with age maching: 1) 60-64; 2) 65-69; 3) 70-74; 4) 75-79; 5) 80-84; 5) 85-89, with inclusion criteria are willing to be respondents and can be measured in the fulfillment of sleep needs and the level of depression. Analysis using Spearman-rank corellation with significance level α <0.05. The results of the study of fulfilling the sleep needs of the elderly at UPT PSLU Bondowoso in the May-June 2014 period were mostly good and bad sleep each of 30 people (40.5%), and a small portion of very good sleep of 3 people (4.1%). Most of the moderate depressions were 34 people (45.9%), and a small proportion were not depressed and severe each as many as 4 people (5.4%). The Spearman-rank corellation test results have a significant relationship between the fulfillment of sleep needs and the level of depression in the elderly in UPT PSLU Bondowoso, with a value of 0,000 (p <0.05). Suggestions for implementing nurses must take care of both because they are interrelated so that they can be preventive activities from the problem